2016
DOI: 10.5194/isprsannals-iii-5-121-2016
|View full text |Cite
|
Sign up to set email alerts
|

3d Central Line Extraction of Fossil Oyster Shells

Abstract: ABSTRACT:Photogrammetry provides a powerful tool to digitally document protected, inaccessible, and rare fossils. This saves manpower in relation to current documentation practice and makes the fragile specimens more available for paleontological analysis and public education. In this study, high resolution orthophoto (0.5 mm) and digital surface models (1 mm) are used to define fossil boundaries that are then used as an input to automatically extract fossil length information via central lines. In general, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…They quantified shell orientations of 527 manually delineated specimens using the 2D centreline of each object. The centreline was automatically derived from oyster boundaries and is defined as an imaginary curved line spanning the maximum length of the shell using the method from Djuricic et al ( 2016c ). The study detected a weak preference for WSW–ENE orientations, but concluded that potential original patterns were biased by post-event processes.…”
Section: Discussionmentioning
confidence: 99%
“…They quantified shell orientations of 527 manually delineated specimens using the 2D centreline of each object. The centreline was automatically derived from oyster boundaries and is defined as an imaginary curved line spanning the maximum length of the shell using the method from Djuricic et al ( 2016c ). The study detected a weak preference for WSW–ENE orientations, but concluded that potential original patterns were biased by post-event processes.…”
Section: Discussionmentioning
confidence: 99%